Food contact surfaces and food handler's hygiene in one Serbian retail chain–estimation and trend. Issue 1 (October 2021) - Jovanovic, J; Nikolic, A; Brankovic Lazic, I; Mrdovic, B; Raseta, M; Lilic, S; Geric, T
Abstract: This research aimed to investigate the efficiency of sanitary procedures (cleaning, washing, disinfection) applied on food contact surfaces and food handlers' hands in one retail chain in Serbia. For that reason, a total of 364 swabs of food contact surfaces and 86 food handlers' hand swabs were investigated for microbiological parameters of process hygiene. The results showed that 15.66% (57 of 365) swabs of food contact surfaces, and 5.81% (5 of 86) swabs from the food handlers' hands, failed to meet the criteria laid down in the self-control plans of the food business operators. Therefore, continuous training of employees on the proper application of sanitation procedures is essential for efficient GHP and HACCP.